PENGARUH LITERASI SOSIOLOGI PENDIDIKAN GURU TERHADAP IMPLEMENTASI PEMBELAJARAN INKLUSIF BERDIFERENSIASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Rika Irawati; Sanseni Safitri; Yeni Karneli; Zelhendri Zen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational sociology literacy is a foundational yet underexplored teacher competency that enables responsive, equitable instruction in diverse classrooms. This study examines the effect of teachers' educational sociology literacy on the implementation of differentiated inclusive learning, classroom diversity management, and student academic achievement in elementary schools. Grounded in Bourdieu's cultural capital theory and symbolic interactionism, a correlational survey design was employed involving 120 Grade IV–VI students from three elementary schools in Mentawai Regency, West Sumatra, selected through cluster random sampling. Data were gathered using a validated questionnaire (Cronbach's α = 0.87; CFA factor loadings > 0.50) and end-of-semester report card scores. Multiple regression analysis confirmed all classical assumption tests (Shapiro-Wilk normality p > 0.05; VIF = 1.23–1.87; Breusch-Pagan χ² = 4.21; p = 0.24). Results revealed that teachers' educational sociology literacy significantly predicted differentiated inclusive learning (β = 0.62; p < 0.001), diversity management (β = 0.54; p < 0.001), and student achievement (β = 0.48; p < 0.001), with the full model accounting for 64% of achievement variance (R² = 0.64; F(3,116) = 68.74; p < 0.001). Effect size qualified as large by Cohen's criterion (f² = 0.89). This study contributes a novel empirically validated framework linking sociological teacher literacy to Merdeka Curriculum-aligned differentiated instruction in archipelago contexts. Findings call for systematic integration of educational sociology into PGSD curricula and teacher professional development programs in high-diversity regions.